Villa Romana Preisträger 1988. - Conzen-Meairs, Ina (Stuttgart : Staatsgalerie Stuttgart, 1987)
Brückner, Nikifor ; Dauerer, Gabriela ; Kütz, Walter ; Schmetz, Klaus ; Böhmer, Karl ; Harr, H.P. ; Haypeter, Werner ; Motte, Uschi ; Pokorny, Werner ; Boschek, Ingrid ; Simon, Klaus
Villa Romana Preisträger 1988, Staatsgalerie Stuttgart, 21. November 1987 bis 6. Januar 1988
kunstcatalogus